Grandpas Are for finding Worms - Harriet Ziefert (U.S.A Puffin Books, 2000)
When you need worms for fishing, Grandpa knows just where to look. Grandpas are great at making things, like bookshelves, burgers, and funny faces. Some grandpas like to sing old songs, some like to play baseball, and all grandpas make you feel special. Young children and grandpas alike will love this sweet tribute to the special love between them
Keywords: Read Aloud -- Read Aloud